HARMONISASI KEARIFANLOKALTERHADAP IMPLEMENTASI PENDIDIKANKARAKTER DI SANGGAR ANAKALAM YOGYAKARTA - Dwi Susanto (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2016)
Harmonization of local knowledge will be a lake that never subsided in the long dry season, when the values of wisdom for the realization of the ideals of the nationâ€™s balance maintained by all elements in a society both physically and mentally. In addition to functioning as a filter for the values come from outside, local knowledge may give rise to a strong passion to apply them in social life. Sanggar Anak Alam Yogyakarta has harmonization in implementing character education through nature and local wisdom. The concept of learning at the Sanggar Anak Alam Yogyakarta is based on the natural environment, so that the environment is a key to the success of learning. Therefore, the value of environmental care and harmonization of local knowledge is one of the principal characters were implanted and developed in this school. The purpose of this study is to analyze how to harmonize the local knowledge that exists in the implementation of the character values in Sanggar Anak Alam Yogyakarta. The method used is a qualitative research method descriptive exploratory naturalistic. Based on the analysis of data and discussion can be concluded that the established harmonization good local knowledge of the implementation of character education in Sanggar Anak Alam Yogyakarta. This takes place both planting and caring character development environment in the Sanggar Anak Alam Yogyakarta or structured activities outside learning. Planting and character development to the values of local wisdom to do with the formation of the student mindset through the appreciation of food, health, education, arts and culture are integrated in the regular activities of the school.Â